Proteomic analysis of chick embryonic heart in experimental hypoxia - Sedmera, David; Drobna Krejci, Eliska; Nanka, Ondrej; Eckhardt, Adam (Developmental biology, 2025)
Investigating prenatal hypoxia is difficult in mammals, as there are confounding factors stemming from maternal adaptations and compensatory mechanisms. We have thus established an avian model of hypoxic incubation (starting after 2 days of normoxia, 15% O2, normobaric, until the time of sampling at embryonic day 8) to study embryonic reactions to low oxygen concentration. Our previous studies have shown increased vascularization, oedema, and ventricular wall thinning preceding the lethality at mid-gestation. Analysis of the cardiac proteome after 6 days of hypoxic incubation showed strong upregulation of enzymes involved in anaerobic glycolysis as well as an increase in apoptosis-related proteins, cell adhesion proteins, and secretory activity.
Keywords: Chick Embryo; apoptóza; hypoxie; proteom; myokard; Proteome; glykolýza; Glycolysis; Animals; Myocardium; Hypoxia; zvířata; Heart; Apoptosis; Proteomics; proteomika; srdce; kuřecí embryo